Clinical and Epidemiological Features of Hospitalized and Ambulatory Patients with Human Monkeypox Infection: A Retrospective Observational Study in Portugal - Caria, J (2022)
Monkeypox, a neglected and re-emergent zoonotic disease caused by monkeypox virus (MPXV) infection, has been endemic in Central and Western Africa for decades. More recently, an outbreak has spread to a global level, occurring in sites with no previous reported cases and being clustered among men who have sex with men, suggesting new modes of transmission. There is an urgent need for research for a better understanding of the genomic evolution and changing epidemiology of the Orthopoxvirus group. Our work aimed to characterize the clinical and epidemiological features of a cohort of patients with MPXV infection in a Portuguese hospital, admitted between 5 May and 26 July 2022. In this retrospective observational study, aggregate data of a case series on the presentation, clinical course, and outcomes of confirmed MPXV infections are reported. The study included 40 men and 1 woman, with a mean age of 37.2 years old; 92.7% identified as men who have sex with men, 90.2% had unprotected sex or sex with multiple or anonymous partners in the previous month, and 39.0% reported to have had sex with an MPXV-confirmed case; 59.5% had previously known human immunodeficiency virus (HIV) infection, all of whom were under antiretroviral therapy, and no patients had acquired immunodeficiency syndrome (AIDS) criteria. About a quarter of patients were observed only a week after symptom onset. All patients had skin or mucosal lesions and the anogenital region was the most frequent lesion site. There were no statistically significant clinical differences between HIV-positive and negative individuals. Four patients were admitted to the inpatient clinic, two of whom had proctitis with difficult-to-manage anal pain. There were no reported deaths. Our findings suggest the sexual route as a relevant mode of transmission of MPXV and confirm the mostly benign presentation of this disease.